Waqf Forest Development Strategy in Cibunian Bogor - Munandar, Asep Nurimam; Pakkana, Mukhaer; Amrizal, Amrizal (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
Indonesia has a significant waqf potential. However, its realization has not been optimal. Using the Bogor Waqf Forest Foundation as the case study, this research analyzes the implementation of the waqf forest development strategy. It assesses the priority Benefits, Opportunities, Costs, and Risks (BOCR) faced. This study uses the business model canvas (BMC) to the BOCR by mapping the nine business blocks of the canvas model. The study finds that the main priorities to strengthen the management and development of the forest waqf project are 1) nāẓir professionalism and competence in knowledge of waqf laws, 2) research and discourse development, and 3) personal approach to collecting waqf funds. Abstrak. Indonesia memiliki potensi wakaf yang signifikan, namun realisasinya belum optimal. Dengan memilih Yayasan Hutan Wakaf Bogor sebagai studi kasus, penelitian ini menganalisis implementasi strategi pengembangan hutan wakaf dan menilai prioritas manfaat, peluang, biaya, dan risiko (BOCR) yang dihadapi. Kajian ini menerapkan business model canvas (BMC) pada BOCR, dengan memetakan sembilan blok BMC. Studi ini menemukan bahwa prioritas utama untuk memperkuat pengelolaan dan pengembangan proyek wakaf hutan adalah 1) profesionalisme nāẓir dan kompetensi dalam pengetahuan hukum wakaf, 2) penelitian dan pengembangan wacana, dan, 3) pendekatan personal dalam pengumpulan dana wakaf